Coastal moderation of Holocene fire and vegetation change on the Pacific coast of Canada - Duncan, Maggie E.; Pellatt, Marlow G.; Kohfeld, Karen E. (Frontiers in Ecology and Evolution, 2025)
In the coming century, climate variability is projected to increase in Northeast Pacific coastal areas, increasing the need for land managers to understand how ecosystems are expected to change in response to new or enhanced disturbances. Previous research indicates that the Pacific coast of Canada, southern British Columbia (BC) experienced warmer and drier climate conditions than present, with higher than modern fire activity during the early Holocene xerothermic interval (9.5 – 7.0 kcal BP). In this study, we reconstructed past climate-fire-vegetation changes from a 13,000-year sediment record from Lost Lake in Vancouver’s Lower Seymour Conservation Reserve, BC. Contrary to other sites, the coastal western hemlock forest at this site remained cool and moist with low fire activity throughout the xerothermic period. Instead, peak fire frequencies were observed during the cool and moist Neoglacial period (4.5 kcal BP – present), when human activity became prevalent. These results have implications for the managed watershed’s resilience to fire and response to future warming conditions.